Inappropriateness of intravenous antibiotic prescriptions at hospital discharge at a tertiary care hospital in Thailand - Tuanjai Mahatumarat (2020)
© 2019 Mahatumarat et al. Background: Intravenous antibiotics, either as outpatient parenteral antimicrobial therapy (OPAT) or transition of care to community-based management, is a common practice in tertiary care hospitals to minimize hospital stays. However, infectious disease consultation was not mandated for those prescriptions. Therefore, we conducted this study to evaluate the appropriateness of intravenous antibiotic prescriptions at hospital discharge. Methods: This retrospective cross-sectional study was conducted among patients receiving care at the internal medicine units of the Maharaj Nakorn Chiang Mai Hospital from November 1, 2015, to April 30, 2016. Intravenous antibiotics at hospital discharge were reviewed by an infectious diseases (ID) specialist. Results: One hundred and twenty-nine prescriptions for 117 patients were reviewed. The most common diagnoses requiring intravenous antibiotics at hospital discharge were upper urinary tract infection (34.2%) and hepatobiliary tract infections (15.4%). The most common intravenous antibiotic was ceftriaxone (36.4%), followed by ertapenem (20.1%). Overall, the inappropriateness of prescriptions was 85.3%. The most common reason for inappropriateness was a failure to switch to oral antibiotics (52.7%), followed by incorrect duration (16.3%). Conclusion: Antimicrobial stewardship should be considered for intravenous antibiotics at hospital discharge to reduce the inappropriateness of those prescriptions.